Study on the absolute configuration and biological activity of rotenoids from the leaves and twigs of Millettia pyrrhocarpa Mattapha, Forest & Hawkins, sp. Nov - Suda Sananboonudom; Atchara Kaewnoi; Wilart Pompimon; Samroeng Narakaew; Suwadee Jiajaroen; Kittipong Chainok; Narong nuntasaen; Kanoknetr Suksen; Arthit Chairoungdua; Jitra Limthongkul; Chanita Naparswad; Suttiporn Pikulthong; et al. (BMC, 2023)
Abstract Background M. pyrrhocarpa is a new plant in the Fabaceae: Faboideae family that is found in Thailand. A literature search revealed that the Milletia genus is rich in bioactive compounds possessing a wide range of biological activities. In this study, we aimed to isolate novel bioactive compounds and to study their bioactivities. Methods The hexane, ethyl acetate, and methanol extracts from the leaves and twigs of M. pyrrhocarpa were isolated and purified using chromatography techniques. These extracts and pure compounds were tested in vitro for their inhibitory activities against nine strains of bacteria, as well as their anti-HIV-1 virus activity and cytotoxicity against eight cancer cell lines. Results Three rotenoids, named 6aS, 12aS, 12S-elliptinol (1), 6aS, 12aS, 12S-munduserol (2), dehydromunduserone (3), and crude extracts were evaluated for antibacterial, anti-HIV, and cytotoxic activities. It was found that compounds 1-3 inhibited the growth of nine strains of bacteria, and the best MIC/MBC values were obtained at 3/ > 3 mg/mL. The hexane extract showed anti-HIV-1 RT with the highest %inhibition at 81.27 at 200 mg/mL, while 6aS, 12aS, 12S-elliptinol (1) reduced syncytium formation in 1A2 cells with a maximum EC50 value of 4.48 μM. Furthermore, 6aS, 12aS, 12S-elliptinol (1) showed cytotoxicity against A549 and Hep G2 cells with maximum ED50 values of 2.27 and 3.94 μg/mL. Conclusion This study led to the isolation of constituents with potential for medicinal application, providing compounds (1-3) as lead compounds against nine strains of bacteria. The hexane extract showed the highest %inhibition of HIV-1 virus, Compound 1 showed the best EC50 in reducing syncytium formation in 1A2 cells, and it also showed the best ED50 against human lung adenocarcinoma (A549) and human hepatocellular carcinoma (Hep G2). The isolated compounds from M. pyrrhocarpa offered significant potential for future medicinal application studies.